The Court of Roberts (the United States Supreme Court) versus the peruvian Constitutional Court: free competition in constitutional jurisprudence - Sumar Albujar, Oscar (2015)
Within the framework of the process of constitutionalization of Law, the treatment towards antitrust  regulation is being discussed on the jurisprudential level. An idea has appeared that suggests that deciding against antitrust regulationis  beneficial for companies, but has a negative impact towards societyIn the present article, the author does a comparison between the Peruvian Constitutional Court jurisprudence about antitrust and the jurisprudence of the Supreme Court of the United States, demonstrating that tending towards regulation is harmful for society.The author also raises the question about the reasons for which the Supreme Court of the United States has a clear and defined criteria to decide when it is convenient to regulate antitrust, called “decision theory”, while the Peruvian  Court  has an erratic and unjustified criteria to decide aboutregulation of antitrust.